THE TOURISM PRACTICES OF THE ASIAN TOURIST IN BALI - A. A. Ayu Arun Suwi Arianty (Institut Pariwisata dan Bisnis Internasional, 2013)
As a widespread tourists destination, Bali in 2011 the international tourists arriving in Bali were increasing around 1.437.725 pax. Especially Asian tourists, they are the major tourists who came to Bali between 2007 and 2011. In view of the Asian tourist become increasingly choosing Bali as a tourists destination, this research will concern about Who are the Asian tourists in Bali? What are their activities in Bali, according to their nationalities? Third, Do the Asian tourists who come from different countries doing the same activities? Fourth,Â Are their motivation, perceptions, representations, and ways to travel are the same according to their origin country? This research will combine both of qualitative and quantitative methods by reason of heighten the result of the research. In addition to enriched the result, in this research also supported by the literatures both printed or online those are in line with the grand theme of the research.